Efficient markets and behavior of economic agents (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
Based on the dual character of the agents (optimization and coordination) we work two statistical models called Overreaction (Contingency Tables) and Underreaction (Event Studies) and we find that the results obtained would overcome the markets gains if we had followed a port folio composed by stocks of the representative  index. Therefore we may affirm that market prices could not reflect the fundamental assets value, since it is possible to improve the benchmark.